If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8p + -23) = 55 Reorder the terms: -1(-23 + 8p) = 55 (-23 * -1 + 8p * -1) = 55 (23 + -8p) = 55 Solving 23 + -8p = 55 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -8p = 55 + -23 Combine like terms: 23 + -23 = 0 0 + -8p = 55 + -23 -8p = 55 + -23 Combine like terms: 55 + -23 = 32 -8p = 32 Divide each side by '-8'. p = -4 Simplifying p = -4
| -(14-7b)=-49 | | x*2-121= | | 6x*2+x-12= | | 2xy+5y-7=0 | | 3-2(x+2)=7 | | 2(x-6)-4(x+2)=-6 | | 0.66x-2=3 | | x+12=7y | | 1+5(2x+3)=6 | | X+a=4 | | -2=-2a+3a | | 8+6(n-3)= | | (2x^2+25x-42)=0 | | 2t+1=19 | | C^2+16c+60=0 | | x+1/11=7/11 | | (x+25)+(y-169)=196 | | y=-0.70(50)+123 | | 0=-16x^2+40x+5 | | y=-0.70(40)+123 | | 4-3(5x-1)=22 | | y=-0.70(30)+123 | | 10x-256=2x+272 | | y=-0.70(20)+123 | | 10-256=2x+272 | | -4x-10-x=2 | | 435+5x=141+23x | | y=0.70(50)+123 | | 72-24x=152-17x | | y=0.70(40)+123 | | -9(x+3)+3x+7=5x+7 | | y=0.70(30)+123 |